Relationship of self-efficacy levels and codependency in a group of relatives of drug addicts patients - Guevara Ortega, Gilmar (2002)
In the present investigation the levels of self-efficacy and the relatives of patient drug addict Codependencia are studied that are receiving treatment in Therapeutic Communities of Metropolitan Lima. The sample this conformed by 115 relatives of patients that have dependence problems to substances like alcohol, he/she pastures basic of cocaine, hydrochlorate of cocaine and marihuana. The instruments used for the present investigation are: The Scale of Codependency of Spann-Fischer and the Scale of widespread self-efficacy of Babler-Schwarzer. Both they allow us to evaluate the levels of Codependencia the first one and self-efficacy the second. The psicometric analysis one carries out based on the factorial analysis, and the consistency goes into it established using the coefficient of dependability Alpha of Cronbach. The results demonstrate us that a significant relationship exists between the codependency and the self-efficacy, as well as some variables as age, time of treatment and instruction level are related significantly with the codependency. Others as the instruction level, time of internment has significant relationship with the codependency.